Occurrence of Yam Mosaic Virus and Yam Mild Mosaic Virus on Dioscorea spp. Germplasm Collection in Cuba—Epidemiology of Associated Diseases - González Ramírez, José Efraín; Cabrera Mederos, Dariel; Ventura Chávez, Vaniert; González Vázquez, Rosa Elena; Ojito-Ramos, Katia; García Romero, Liset; Salazar-Garcés, Luis Fabián; Velastegui-Hernández, Diana Catalina; Hernández Navarro, Elena Vicenta; Leiva-Mora, Michel; Giolitti, Fabian; Portal, Orelvis (MDPI, 2024)
Potyvirus diseases are one of the main challenges facing the production of yam (Dioscorea spp.). The objective of this study was to identify the potyviruses present in the Dioscorea spp. germplasm collection at Instituto de Investigaciones de Viandas Tropicales (INIVIT) to establish methodologies for the characterization of the associated diseases. For this purpose, immunochemical and molecular methods were used to identify the potyviruses present. The symptomatology of Dioscorea spp. at INIVIT’s germplasm collection was described. In addition, the severity and incidence in the germplasm collection and production areas were evaluated. As a result, the first report of yam mosaic virus (Potyvirus yamtesselati) and yam mild mosaic virus (Potyvirus yamplacidum) in Cuba is presented. The existence of resistant, tolerant, and susceptible cultivars to potyvirus-associated diseases in the germplasm collection was detected, and the incidence of these diseases was higher than 64% in the production areas evaluated. This study represents a step forward in the establishment of certification programs for propagating material of Dioscorea spp. in Cuba.